Macro-assembly of the ATLAS barrel SCT - Viehhauser, G (2004)
Like all LHC detector construction projects the assembly of the barrel section of the ATLAS Semiconductor Tracker (SCT) is well advanced. In particular the mounting of the 2112 Silicon strip detectors onto the four cylindrical barrel support structures (ATLAS SCT barrels 3-6) is now taking place at Oxford University. In this paper we present the various procedures required in the assembly of the detector modules onto the support structure and the performance verification of the completed barrels. We will report on experiences and observations we have made during these activities and the results obtained in the various performance verification tests. © 2004 IEEE.